Pembudayaan Nilai-Nilai Pancasila pada Penderita Penyakit Tuberkulosis - Supriyanto Supriyanto; Masrukhi Masrukhi (Jurnal Surya Masyarakat, 2021)
This program aims to build public awareness of the values of Pancasila in preventing Tuberculosis. Community service activities were carried out on Friday 4 September 2020 at the multipurpose building Aisyiyah Batang, Jl. Wahid Hasyim, Kauman Batang. The participants of the activity were 44 health cadres who were representatives of all sub-districts in the Batang Regency.. This community service method is carried out by providing socialization and education to the people of Batang Regency. Results of this community service are: 1) the increase in the cultivation of Pancasila values in patients with tuberculosis in Batang Regency, 2) the increase of public awareness of the values of Pancasila in the prevention of Tuberculosis, 3 )the capability of the community to keep the environment clean and avoid environmental pollution according to the values of Pancasila, and 4) the increase of the sense of concern among members of the community for tuberculosis sufferers according to values. In addition, community participation in the culture of Pancasila values in tuberculosis patients has increased. The conclusions are: 1) the cultivation of Pancasila values can increase public awareness in preventing Tuberculosis, 2) through community service activities regarding the culture of Pancasila values, the community is able to maintain personal and environmental hygiene to prevent Tuberculosis, and c) community service activities regarding the culture of Pancasila values can increase the sense of concern among community members towards people who are sick with Tuberculosis. Therefore, through the cultivation of Pancasila values, especially the second principle, a just and civilized humanity becomes very important. The culture of Pancasila values in people with tuberculosis is one of the state's efforts to protect citizens.